2018
DOI: 10.1039/c8ra01683f
|View full text |Cite
|
Sign up to set email alerts
|

Novel dual-site fluorescent probe for monitoring cysteine and sulfite in living cells

Abstract: A dual-site fluorescence probe LC-1 was developed for the detection of Cys and SO32−.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Furthermore, BPO-DNSP can not only be used for imaging intracellular SO 2 and biothiols, but can also be used for monitoring the conversion from biothiols to SO 2 without adding exogenous enzymes, which can help us better understand the physiological nature of RSS. In comparison with the reported probes [24,25,26,27,28] for two-channel imaging of SO 2 and biothiols, BPO-DNSP exhibited three advantages for bioimaging: (1) as far as 170 nm emission shift from two different channels; (2) near-infrared wavelength detection of intracellular biothiols; and (3) monitoring the conversion from biothiols to SO 2 without adding exogenous enzymes. Moreover, BPO-DNSP revealed its superiority in biological applications as it avoids potential interference compared with reported probes using an aldehyde group as a reaction site.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, BPO-DNSP can not only be used for imaging intracellular SO 2 and biothiols, but can also be used for monitoring the conversion from biothiols to SO 2 without adding exogenous enzymes, which can help us better understand the physiological nature of RSS. In comparison with the reported probes [24,25,26,27,28] for two-channel imaging of SO 2 and biothiols, BPO-DNSP exhibited three advantages for bioimaging: (1) as far as 170 nm emission shift from two different channels; (2) near-infrared wavelength detection of intracellular biothiols; and (3) monitoring the conversion from biothiols to SO 2 without adding exogenous enzymes. Moreover, BPO-DNSP revealed its superiority in biological applications as it avoids potential interference compared with reported probes using an aldehyde group as a reaction site.…”
Section: Discussionmentioning
confidence: 98%
“…To better understand their physiological nature and cellular cross-talk, a single fluorescent probe with dual functions could provide more detailed information about the microenvironment and physical condition of the cells [24]. However, there are still few fluorescent probes presented for imaging SO 2 and biothiols with distinct responses from different emission channels [25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The other select anions and structurally similar sulfur-containing oxyanions (1000 μM; Figure 4c) does not exerted any noticeable variation to the SO 3 2À -actuated spike in the native fluorescence profile of D. Concomitantly, a probable alteration in the fluorescence of D by nucleophilic biothiols (Cys, Hcys and GSH; 1000 μM) was also negligible, thereby ruling out a possible interference from the latter in the effective sensing of sulfite ions by D (Figure 4d). [38,39] Therefore, it could be concluded that the molecule D offers a discriminating behavior towards SO 3 2À ions from its chemically close sulfur associates via selectively sensitive fluorescence stimulation.…”
Section: Chemistryselectmentioning
confidence: 96%